APAKAH PASIEN SKIZOFRENIA MERAWAT KEBERSIHAN GIGI DAN MULUTNYA? - Galuh Dwinta Sari; Chandra Wijaya; R. Harry Dharmawan Setyawardhana; Aulia Azizah (Universitas Lambung Mangkurat, 2025)
ABSTRACTBackground: Mental disorders can have a major impact on life and have a negative impact on social interactions. South Kalimantan Province has a prevalence of 5.1% of household members experiencing mental disorders. People with mental disorders have manifestations of psychomotor disorders such as limitations in movement and activities which can trigger dental and oral health problems such as caries. Objective: To determine the description of the severity of caries in patients with mental disorders at Sambang Lihum Hospital. Method: Quantitative descriptive research with cross sectional design. The sampling technique uses simple random sampling. The population is mental patients who are treated and are undergoing rehabilitation therapy at the Sambang Lihum Hospital as many as 127 people. The sample size by Slovin formula which obtained the results of 62 respondents. Results: Based on the DMF-T examination, the caries severity level of the respondents was in the very high category with a DMF-T frequency of 856 and a DMF-T index of 13.8. The caries index in men and women has a very high category. The highest DMF-T index and frequency distribution were in the age group >65 years. Psychiatric diagnoses with the highest DMF-T index were diagnoses of schizophrenia, schizotypal disorder, and delusions with a DMF-T frequency of 505 and a DMF-T index of 14.85. Conclusion: The average caries severity rating of patients with mental disorders at Sambang Lihum Hospital is in the very high category with the highest diagnoses belonging to those with a diagnosis of schizophrenia, schizotypal disorder and delusions.Keywords: caries severity, mental disorders, schizophrenia ABSTRAK Latar Belakang: Gangguan mental dapat berpengaruh besar bagi kehidupan dan berdampak buruk pada interaksi sosial. Provinsi Kalimantan Selatan memiliki prevalensi 5,1% anggota rumah tangga yang mengalami masalah gangguan jiwa. Orang dengan gangguan jiwa memiliki manifestasi gangguan psikomotor seperti keterbatasan bergerak dan beraktivitas yang dapat memicu timbulnya masalah kesehatan gigi dan mulut seperti karies. Tujuan: Mengetahui gambaran tingkat keparahan karies pasien dengan gangguan jiwa di RSJ Sambang Lihum. Metode: Penelitian deskriptif kuantitatif dengan desain cross sectional. Teknik pengambilan sampel menggunakan simple random sampling. Populasi adalah pasien gangguan jiwa yang dirawat dan sedang menjalani terapi rehabilitasi di RSJ Sambang Lihum sebanyak 127 orang. Besar sampel dihitung dengan menggunakan rumus slovin yang diperoleh hasil sebanyak 62 responden. Hasil: Tingkat keparahan karies berdasarkan pemeriksaan DMF-T pada responden memiliki kategori sangat tinggi dengan frekuensi DMF-T sebesar 856 dan indeks DMF-T sebesar 13,8. Indeks karies pada laki-laki dan perempuan memiliki kategori sangat tinggi. Distribusi frekuensi dan Indeks DMF-T tertinggi berada pada kelompok usia >65 tahun. Diagnosis kejiwaan dengan indeks DMF-T tertinggi berada pada diagnosis skizofrenia, gangguan skizotipal, dan waham dengan frekuensi DMF-T sebesar 505 dan indeks DMF-T sebesar 14,85. Kesimpulan: Gambaran tingkat keparahan karies pasien dengan gangguan jiwa di RSJ Sambang Lihum rata-rata berada pada kategori sangat tinggi dengan diagnosis tertinggi dimiliki oleh mereka yang didiagnosa skizofrenia, gangguan skizotipal dan waham.Kata Kunci: gangguan jiwa, keparahan karies, skizofrenia